A Female Patient With Clinical Symptoms as Recurrent Urinary Tract Infection Caused By Urinary Tract Tuberculosis - Rastita Widyasari; Artaria Tjempakasari; Chandra Irwanadi Mohani (Universitas Airlangga, 2020)
Background : Urinary tract tuberculosis (TB) is one type of extrapulmonary TB. The prevalence in developed countries is around 15-20% of all cases of extrapulmonary TB.1 The insidious onset and non-specific constitutional symptoms of urinary tuberculosis often lead to delayed diagnosis and rapid progression to a non-functioning kidney.2-3 The only way to limit renal function loss and destruction is by early diagnosis and therapy.4Case: 34-year-old woman, came with complaints of urinary pain accompanied by right flank pain 10 months prior. Patient also had complaint of weight loss but ignoring complaints of night sweats. Patient repeatedly diagnosed as a urinary tract infection and received many kinds of antibiotic therapy but her complaints were not getting better. Urine production was about 1700 cc/24 hours. From general physical examination, there was a lack of nutritional status with BMI 17.1 kg/m2. Vesicular lung sound without rhonchi heard in both lung fields. From the urinalysis examination there were pyuria and haematuria without bacteriuri. Laboratory examination showed value of BUN was 17 mg/dl and creatinine 0.9 mg/dl. From aerob urine culture we found sterile urine. But we found positive result of Mycobacterium tuberculosis (MTB) urine cultures which was sensitive to isoniazid, rifampicin, pyrazinamide, and ethambutol. Abdominal ultrasound showed severe ecstasis of right pelviocalyceal system without stones,mass, nor cyst. We had additional data from intravenous pyelogram (IVP) which showed a non-visualized dextra pelviocalyceal system and delayed bladder emptying function at 120th minutes. From computed tomography stonographic, we found severe right hydronephrosis, proximal to distal right hydroureter, and thickening of bladder wall (± 1.61 cm) on the right antero-lateral side. To find out the cause of thickening of bladder wall, we did bladder biopsy which showed the mononuclear inflammatory cell stroma. Patients were diagnosed with urinary tract TB and received category 1 of oral anti tuberculosis therapy (Rifampicin, Isoniazid, Pyrazinamid, and Ethambutol) for 12 months and underwent right DJ stent implantation to manage the ectasys.Conclusion : Urinary tract TB often showed unspecified complaints and can be suggested as recurrent urinary tract infections. Early diagnosis and optimal management were needed to prevent anatomical and functional complications.